2021
DOI: 10.1002/mde.3308
|View full text |Cite
|
Sign up to set email alerts
|

Do professional norms in the medical industry favor outcome bias?

Abstract: This study tests the effect of doctors' professional identity on their outcome bias. We conduct a medical experiment with 264 doctors, a robustness test with 105 doctors, and a public experiment with 170 non‐doctors. The experimental results show that doctors, but not non‐doctors, exhibit more outcome bias when we exogenously render their professional identity more salient. These results indicate that professional norms in the medical industry favor outcome bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The medical decisions outcome bias scenario that we aimed to replicate from the target received follow-up research extending the phenomenon beyond the lab and examining moderating factors. For example, it has been suggested that outcome bias is weakened by seniority (Liaw et al, 2019) and strengthened by salience of professional identity (Fan et al, 2021). Medical decisions involve a unique information asymmetry on the part of patients, who have less expertise and experience and are less familiar with the base rates used to inform their decisions (Bar-Hillel, 1980).…”
Section: Broader Importance Of Outcome Biasmentioning
confidence: 99%
“…The medical decisions outcome bias scenario that we aimed to replicate from the target received follow-up research extending the phenomenon beyond the lab and examining moderating factors. For example, it has been suggested that outcome bias is weakened by seniority (Liaw et al, 2019) and strengthened by salience of professional identity (Fan et al, 2021). Medical decisions involve a unique information asymmetry on the part of patients, who have less expertise and experience and are less familiar with the base rates used to inform their decisions (Bar-Hillel, 1980).…”
Section: Broader Importance Of Outcome Biasmentioning
confidence: 99%